Working conditions at workplaces in finishing operations departments of foundries - A. M. Lazarenkov; M. A. Sadokha; A. A. Novik (Литьë и металлургия)
The working conditions at the workplaces of foundry workers when performing finishing operations, production factors determining them are considered. The results of studies of the parameters of the working conditions of the considered professions of foundry workers in comparison with the standard values are presented. It has been established that in a comprehensive assessment of the working conditions of foundries working in the department of financial operations, it is necessary to take into account the duration of stay at the working equipment, the equipment and hand tools used, the type of alloy being smelted (steel, cast iron, non‑ferrous metals) and the nature of production.